Viewpoint: Towards Integrating Education for Sustainable Development at Initial Teacher Training: The Case of Lesotho College of Education - Mantoetse Jobo (Environmental Association of Southern Africa, 2013)
This viewpoint paper presents some findings of a participatory action research programme carried out by teacher trainers at the Lesotho College of Education (LCE) in order to integrate education for sustainable development (ESD) into its courses. It reveals how social learning brings about deep meaning as students connect subject content knowledge through participatory learning to their sociocultural backgrounds. Participants were later interviewed to ascertain their views on teaching for sustainable development and on interdisciplinary collaboration as a means of enhancing quality in teaching and learning. The findings indicate that some participants had, as a result of the action research project, been able to emerge from the culture of academic isolation through initiating collaboration with other teacher trainers outside the study area.